FORMULASI STRATEGI DALAM MENGEMBANGKAN OBJEK PANTAI TANJUNG BAJAU KOTA SINGKAWANG - Rizky David Lasma Batubara E.01108030 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This Article is written for the purpose of knowing and identifying external and internal factors which influenced the development process of  Tanjung Bajau Beach Singkawang City as a tourism object. This research is done by direct observation and interviewing the person in charge of Tanjung Bajau Beach development. With this research report, the manager of Tanjung Bajau Beach is expected to know which strategy is useful for developing the tourism object further in the future. With knowing and identifying internal and external factors of the tourism object itself, the best strategy that suitable for development the tourism object could be formulated. This research is using SWOT analysis in analyzing the data. With SWOT analysis, the best suitable strategy for  Tanjung Bajau Beach development will be obtained. After the research, the manager of tourism object Pantai Tanjung Bajau could implement the strategy obtained by SWOT analysis that have been done as the result of this research. Key Words : Development Strategy, Tourism Object, Internal Factor, External Factor, SWOT Analysis